Parent–child conversations about refugee newcomers are associated with children's refugee-specific prosociality. (May 2023) - Peplak, Joanna; Jambon, Marc; Bottoni, Alyssa; Malti, Tina
We examined Canadian host-society children's prosociality (i.e., emotions and behaviors that reflect care for the welfare of others) toward refugee newcomer peers and the role of parental socialization (i.e., frequency of parent-child conversations about refugee newcomers) in children's refugee-specific prosociality. The sample included 168 children (ages 6, 9, and 12 years; 51% girls; 58% European ethnicity) and their primary caregivers. We interviewed children to assess their ethical guilt-related emotions (based on emotions and reasoning) in response to a hypothetical vignette depicting prosocial omission involving a refugee newcomer peer or a non-refugee peer (between-subjects manipulation). A donation task was used to assess prosocial behavior wherein children were given the opportunity to donate chocolate coins to a refugee newcomer peer. Parents reported on how often they typically engage in conversations with their children about refugees and about inclusion. Children experienced similar intensities of ethical guilt-related emotions in the refugee compared with the nonrefugee condition, and donations to refugees increased across age groups. Furthermore, children whose parents engaged them in more frequent conversations about refugees expressed stronger ethical guilt-related emotions toward refugee peers (but not toward host-society peers), and donated more to a refugee peer. No significant associations between conversations about inclusion more broadly and refugee-specific prosociality were found. Encouraging parents to have conversations with their children that focus on the experiences of refugees may be important for fostering kindness between refugees and host-society children. Ultimately, these findings may contribute to initiatives that focus on promoting the inclusion of refugee newcomers in their postmigratory societies.